The Principle of Proportionality: Separating the Impact of Dual Class Shares, Pyramids and Cross-ownership on Firm Value Across Legal Regimes in Western Europe - Morten Bennedsen; Kasper Meisner (Copenhagen Business School (CBS), Department of Economics, 2006)
Recent policy initiatives within the harmonization of European company laws have promoted a so-called "principle of proportionality" through proposals that regulate mechanisms opposing a proportional distribution of ownership and control. We scrutinize the foundation for these initiatives by analyzing the use of instruments to separate ownership from control across legal regimes in a sample of over 4,000 publicly traded firms from 14 Western European countries. First, we confirm the negative impact on firm value from disproportional ownership structures previously established in a sample of Asian firms by Claessens et al. (2002). Second, we show that dual class shares have a larger and more significant negative effect on firm value than pyramids and cross holdings. Third, we find that the impact of disproportionality and the underlying instruments is inversely related to the level of investor protection. Thus, dual class shares and pyramids substitute legal protection in countries with inadequate investor protection. Fourth, we find no evidence of a significant effect of disproportionality instruments on earnings performance. Finally, we discuss policy implications of these findings in relationship to the process of harmonization of the European capital markets.
hdl:10398/7544
Keywords: G30; G32; G34; G38; 330; Ownership Structure; Dual Class Shares; Pyramids; EU company